Folk Heritage and Sustainable Development: A Study on Traditional Dances - Barka BOUCHIBA (Turath)
Cultural heritage is one of the important elements for achieving sustainable development because of its economic, social, cultural and environmental impact. Indeed, it is an axial component working to activate the other sectors, in particular those of tourism, transport, traditional industries and food industries. This will allow small and medium-sized enterprises to grow so that they can offer jobs and attract financial income in local and foreign currency.